PENAMBAHAN LARUTAN KAPUR SIRIH DAN BUBUK KULIT BUAH MANGGIS TERHADAP KUALITAS GULA MERAH DARI NIRA NIPAH - Zulfa Reni; Akhyar Ali; Usman Pato (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2018)
Nypa sap was material for making palm sugar be easily to damage due to microbial contamination. It can be prevented by the addition of lime solution and mangosteen rind powder. The purpose of this research was to determine the effect addition of lime solution and mangosteen rind powder to nypa sap for making palm sugar. This study used Randomized Block Design (RBD) with five treatments and three replications, followed by DNMRT test at 5% level. The treatment for this study were GM1 (2% lime solution), GM2 (2% lime solution and 2,5% mangosteen rind powder), GM3 (2% lime solution and 5% mangosteen rind powder), GM4 (2% lime solution and 7,5% mangosteen rind powder), GM5 (2% lime solution and 10% mangosteen rind powder). Results of research showed that the addition of lime solution and mangosteen rind powder give real effect to moisture content, ash, reducing sugar, sucrose, unsoluble solid, pH and sensory assessment. The best treatment to obtain palm sugar was GM3 with moisture content of 7.82%, ash of 1.65%, reducing sugar of 6.12%, sucrose of 79.25%, unsoluble solid of 1.03%, pH palm sugar of 7.10 and it have hard texture, color brown, sweet, aroma palm sugar and preference test of panelis was like. Keywords: palm sugar, nypa, lime solution, mangosteen rind powder.